Lockdown Fatigue in Pediatric Respiratory Patients: Lessons from the First COVID-19 Year - Michal Cahal; Israel Amirav; Mika Rochman; Moria Be'er; Omri Besor; Moran Lavie (MDPI AG, 2022)
Lockdown policies have been implemented worldwide to limit the spread of COVID-19. "Lockdown fatigue" is a state of exhaustion related to the accumulating effects of repeated lockdowns. The aim of the current study was to examine the effects of repeated lockdowns on children with respiratory disorders. Data on children aged 0-18 years old with respiratory disorders were collected by an electronic survey during the third lockdown in Israel. The retrieved information included demographics and baseline medical status, respiratory clinical status during the third lockdown compared to pre-lockdown periods, lockdown adherence, lifestyle modifications and caregiver emotional status. The results were compared to those of a similar questionnaire distributed during the first lockdown. A total of 234 patients (62% males, 37% females, mean age 6.8 years (confidence interval 6.1-7.5)) were enrolled. Respiratory symptoms and exacerbation frequency were reduced in 76 (35.5%) and 58 (27.4%) patients, respectively, compared to the pre-lockdown period and similar to the first lockdown (p = 0.840 and p = 0.063, respectively). However, compared to the first lockdown, the third lockdown was associated with greater use of reliever medications (p = 0.006), less use of inhaled corticosteroids as routine treatment (p = 0.027), and more pediatric emergency room visits and hospitalizations (p = 0.001 and p < 0.001, respectively). The results also showed an increase in sedentary lifestyle (e.g., reduced physical activity (p = 0.025), less healthy eating habits (p = 0.001)) and reduced adherence to lockdown policies (p < 0.001). These data show that the continuing stability of clinical improvement during lockdown was accompanied by deleterious sequelae that potentially indicate "lockdown fatigue" among children with respiratory disorders.